Basalt fibers coated with nano-calcium carbonate for in-tube solid-phase microextraction and online analysis of estrogens coupled with high-performance liquid chromatography. Issue 19 (30th April 2018) - Wang, Xiuqin; Feng, Juanjuan; Feng, Jiaqing; Tian, Yu; Luo, Chuannan; Sun, Min
Abstract : Estrogens have caused many serious problems due to their serious effects on the environment and organisms. Abstract : Estrogens have caused many serious problems due to their serious effects on the environment and organisms. The aim of this study was to analyze the estrogens in environmental samples using in-tube solid-phase microextraction coupled with high performance liquid chromatography. Nano-calcium carbonate was used as an extraction coating to modify basalt fibers. The scanning electron micrograph clearly showed that the nano-calcium carbonate was successfully attatched to the surface of the basalt fiber. Some factors including the extraction volume, sampling rate, organic solvent content and desorption time were investigated with respect to the extraction efficiency of five estrogens. Under the optimized extraction conditions, a simple and sensitive analytical method was developed, and showed low limits of detection (0.05–0.30 μg L −1 ), wide linear ranges (0.15–20 μg L −1 ), good linearity ( r > 0.9989) and satisfactory repeatability (relative standard deviation < 4.1%). The recoveries of the method for the targets in two water samples ranged from 87% to 120%, with a relative standard deviation of less than 4.9%.